The Effect of Perceived Ease of Use, Usefulness and Risk on Intention to Use the Go-Food Application in Surabaya and Sidoarjo - Bregashtian, Bregasthian; S.E., M.M., CFP2, Dr. Christian Herdinata (KnE Social Sciences, 2021)
This study aimed to determine the effect of perceived ease of use (X1), perceived usefulness (X2) and perceived risk (X3) on the behavioral intention (Z) to use (Y) the Go-Food applications in Mr. Bre’s Geprek Chicken and other similar businesses. This research was quantitative descriptive. Purposive sampling was used and the sample included 100 respondents. An online questionnaire was used for data collection using Google Form and the data were analysed using partial least squares through SmartPLS 3 Software. Perceived usefulness, perceived risk and attitude towards had a significant effect on intention; however, perceived ease of use did not have a significant effect. Keywords: perceived ease of use, perceived usefulness, perceived risk, behavioral intention